Assessment of biological age and "quantity of health" of judoists-veterans at the exit stage from elite sport - Volodymyr Perebeynos; Serhij Pakulin (Kharkiv State Academy of Physical Culture, 2016)
Purpose: the assessment of biological age and "quantity of health" of judoists-veterans that allows estimating the level of functionality of their organism at the exit stage from elite sport and to construct correctly their training and competitive processes. Material & Methods: the systemic-functional approach is applied. The biological age and "quantity of health" of judoists-veterans decided with the help of tests. The group of 28 men and 19 women - judoists-veterans is tested for this purpose. Results: it is proved that the research of biological age of veterans of judo at the exit stage from elite sport, continuing systematic trainings, is of great importance for sports medicine, physical therapy, gerontology, neurology, and also for professional selection in respect of age rationing of intellectual and exercise stresses, assessment of influence of the motive mode on the rate of aging; the carried-out tests allowed to estimate "quantity of health" of judoists-veterans, giving the idea of the level of functionality of their organism. Conclusions: it is proved that judo classes, the correct and positive image of life positively influence health of judoists-veterans.